A Study of Employee Digital Supply Chain Skill Needs and Business School Executive Education Program Coverage of These Skills - Foroughi, Abbas (Archives of Business Research, 2024)
Digital technologies are being widely adopted to bring visibility and efficiency to supply chains, but employees often lack the technology skills needed to use them effectively. This situation presents significant opportunities for business school executive education programs to access new pools of students and remain relevant as a source of employee technology training, even as they face stiff competition from a myriad of online training providers. This study examined business school executive education websites to determine the extent to which they are meeting the digital supply chain training needs of corporate employees. Findings indicate that, although employee format preferences for short, online, customized, flexible courses have been built into executive education programs, a number of critical digital supply chain topics are covered by only a few business school programs or not at all.